Effects of Lactiplantibacillus-plantarum-ZG7-Fermented Feed on Laying-Hen Productivity and Intestinal Health - Zhaolong Li; Wenjing Liu; Huini Wu; Song Peng; Mengshi Zhao; Fengqiang Lin; Lu Zhao (Fermentation)
The improvement in poultry production performance varies with different microbial strains used in fermented feed. This study investigates the efficacy of Lactiplantibacillus-plantarum-ZG7-fermented feed (ZG7-FF) on the productivity of laying hens. Results indicated that ZG7-FF significantly reduced the daily feed intake while increasing egg weight and decreasing the feed-to-egg ratio during peak production (p < 0.05), in addition to enhancing the late-phase laying rate (p < 0.05). Further intestinal morphological results showed that ZG7-FF significantly increased the length of villi in each intestinal segment, most significantly in the duodenum and jejunum (p < 0.01). ZG7-FF also significantly increased the abundance of the phylum Desulfobacterota, while showing a notable increase in the abundance of Cyanobacteria. Conversely, there was a significant reduction in the abundance of intestinal Firmicutes (p < 0.05), specifically Limosilactobacillus and Ligilactobacillus. The LEfSe (LDA Effect Size) analysis indicated that the differential species in the duodenum associated with ZG7-FF are primarily Bifidobacteriales and Aeriscardovia. In contrast, the jejunum is predominantly composed of Cyanobacteria, while the colon is mainly characterized by Enterococcus. Non-targeted metabolomics revealed that ZG7-FF drives the suppression of key metabolites, including 3-hydroxybutyric acid, ethylnitronate, 6-chlorocoumarin-3-carboxylic acid, lotaustralin, and oleoylcarnitine, while enriching pathways related to amino acid metabolism. The downregulated metabolites were functionally linked to ABC transporters and neuroactive ligand–receptor interactions. Correlation analyses demonstrated positive associations between Limosilactobacillus/Ligilactobacillus and suppressed metabolites, whereas Enterococcus and chloroplast-related taxa exhibited negative correlations. In summary, the administration of ZG7-FF significantly enhances intestinal morphology, reduces feed intake, increases egg weight, decreases ingredient usage, elevates the abundance of intestinal Enterococcus, and diminishes the overall microbial load.